Requirements Analysis and Design of an E-Learning System for Learning Digitalization - Dewa Idaman; Surya Ade Saputera; Sri Handayani; Gunawan (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2026)
The learning process at SMA Negeri 3 Bengkulu Selatan is still conducted conventionally, with the management of learning materials, assignments, quizzes, attendance, and grades mostly carried out manually, causing problems such as missed materials when students or teachers are absent, as well as time-consuming manual recapitulation of attendance and grades. This research aims to analyze the functional and non-functional requirements and to produce a design for an e-learning information system based on the Claroline Learning Management System (LMS) platform that suits the school's needs. The method used is descriptive qualitative combined with a waterfall software engineering approach, limited to the analysis and design stages, with data collected through observation and interviews with the Vice Principal for Curriculum, teachers, students, and administrative staff. The results show sixteen functional requirements and seven non-functional requirements translated into a Context Diagram, tiered Data Flow Diagrams (DFD) for eight main processes, an Entity Relationship Diagram (ERD) with twelve entities, and an interface design in which eight of ten functional requirements were verified as fully met and all navigation scenarios were tested according to the design through black box testing. Keywords: information system; e-learning; requirements analysis; system design